2017
DOI: 10.1186/s13059-017-1366-0
|View full text |Cite
|
Sign up to set email alerts
|

Systems-epigenomics inference of transcription factor activity implicates aryl-hydrocarbon-receptor inactivation as a key event in lung cancer development

Abstract: BackgroundDiverse molecular alterations associated with smoking in normal and precursor lung cancer cells have been reported, yet their role in lung cancer etiology remains unclear. A prominent example is hypomethylation of the aryl hydrocarbon-receptor repressor (AHRR) locus, which is observed in blood and squamous epithelial cells of smokers, but not in lung cancer.ResultsUsing a novel systems-epigenomics algorithm, called SEPIRA, which leverages the power of a large RNA-sequencing expression compendium to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 88 publications
5
53
1
Order By: Relevance
“…In addition to the aboveā€mentioned analyses, ChIPā€Atlas Enrichment Analysis (formerly designated ā€œ in silico ChIPā€) has been used for various other purposes. For example, this tool has been applied to analyze TR enrichment at genomic ROIs such as expression quantitative trait loci (eQTLs), a user's own ChIPā€seq peakā€call data, and evolutionarily accelerated regions as well as genes whose expression levels are changed by drug exposure, aging, or cancer development (see http://chip-atlas.org/publications for the full list of publications citing ChIPā€Atlas). The results generated by ChIPā€Atlas are all assigned unique URLs (see ChIPā€Atlas document in https://github.com/inutano/chip-atlas/wiki for details) and are publicly available, and they are thus ready for sharing seamlessly among researchers for subsequent analysis in command lines and for interconnecting with other biodatabases such as the DeepBlue Epigenomic Data Server and RegulatorTrail , where ChIPā€Atlas data have been imported and subjected to analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the aboveā€mentioned analyses, ChIPā€Atlas Enrichment Analysis (formerly designated ā€œ in silico ChIPā€) has been used for various other purposes. For example, this tool has been applied to analyze TR enrichment at genomic ROIs such as expression quantitative trait loci (eQTLs), a user's own ChIPā€seq peakā€call data, and evolutionarily accelerated regions as well as genes whose expression levels are changed by drug exposure, aging, or cancer development (see http://chip-atlas.org/publications for the full list of publications citing ChIPā€Atlas). The results generated by ChIPā€Atlas are all assigned unique URLs (see ChIPā€Atlas document in https://github.com/inutano/chip-atlas/wiki for details) and are publicly available, and they are thus ready for sharing seamlessly among researchers for subsequent analysis in command lines and for interconnecting with other biodatabases such as the DeepBlue Epigenomic Data Server and RegulatorTrail , where ChIPā€Atlas data have been imported and subjected to analyses.…”
Section: Resultsmentioning
confidence: 99%
“…This tool is also able to accept a batch of gene symbols and can therefore discover TFs that collectively regulate the gene set of interest (e.g. Chatterjee et al 2018;Onodera et al 2017;Chen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Because scRNA-Seq is noisy and subject to a high technical dropout rate 5 , and given a recent report which concluded that inferring regulatory relationships from scRNA-Seq is a highly suboptimal procedure 33 , we decided to approach this task differently, by first using a large-scale bulk RNA-Seq dataset to construct an approximate regulatory network. In particular, we here use the GTEX dataset 36 , which consists of bulk RNA-Seq profiles for 8555 samples encompassing 30 tissue types ( Methods ), to infer a regulatory network with our SEPIRA algorithm 37 ( Methods, Fig.1A ). SEPIRA uses a greedy partial correlation framework, similar in spirit to the state-of-the-art GENIE3 algorithm 35, 38 , to infer direct dependencies between regulators and downstream targets.…”
Section: Resultsmentioning
confidence: 99%
“…Using SEPIRA on the GTEX data, we constructed a lung-specific regulatory network, termed ā€œLungNetā€, which consists of 38 lung-specific TFs and a total of 1145 gene targets (range of targets per TF=10 to 152, mean=39.8) ( SI table.S2 , Methods ). We note that LungNet was already constructed and extensively validated by us previously 37 . Since by construction these 38 TFs are more highly expressed in lung tissue compared to all other tissue types and given their established role in lung tissue development 37 , most if not all of these ought to exhibit increased activation in the scRNA-Seq lung development study.…”
Section: Resultsmentioning
confidence: 99%